Edukasi Karakteristik dan Penggunaan Antibiotik untuk Pengobatan Keluarga - Rina Hidayati Pratiwi; Endang Sulistyaniningsih; Jumadi Jepri; Theressia Evy Nadeak; Laksita Nirmala Putri (Universitas Kristen Indonesia Toraja, 2024)
The low level of knowledge about the appropriate use of antibiotics causes the practice of irrational antibiotic use to increase. The aim of this community service is to provide education about understanding antibiotics and how to use them appropriately and rationally. The community service method is by providing education through group discussions, workshops and seminars to health workers, posyandu cadre mothers and the community around Ratujaya Village, Depok. The level of knowledge about antibiotic use was measured using a questionnaire, pretest and posttest. The results achieved by this community service after providing education on understanding antibiotics and their use to the community show that people who have good and sufficient knowledge about antibiotics are 88.57%, meaning that more people understand about antibiotics than those who don't. It can be concluded that the education on the use of antibiotics provided to the public can sufficiently increase public knowledge regarding antibiotics.